Depolarization lidar measurements (Arctic Data Center, 2010)
This data set contains measurements from a Cloud and Aerosol Polarization and Backscatter Lidar (CAPABL) system that is deployed at Summit Station, Greenland. This lidar points near-vertically and measures backscatter in three polarization states. Parameters include: backscatter in the parallel channel, the depolarization ratio, and the diattenuation. Detailed information on these parameters and other aspects of the dataset are included in the netCDF header information for each file. The lidar is owned by the National Oceanic and Atmospheric Administration's Earth System Research Laboratory. Field operations support is provided by the National Science Foundation's Arctic Observing Network (AON) Program.